If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3cosx = 0 Reorder the terms: -3cosx + x = 0 Solving -3cosx + x = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1x' to each side of the equation. -3cosx + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 -3cosx + 0 = 0 + -1x -3cosx = 0 + -1x Remove the zero: -3cosx = -1x Divide each side by '-3osx'. c = 0.3333333333o-1s-1 Simplifying c = 0.3333333333o-1s-1
| 96=-8(n-8) | | 30x+25y=275 | | cosx-3sinx=2 | | 5/9*p=-10 | | -3x+1=4x-34 | | 5x+4(5x+3)=-13 | | -96=-8(n-8) | | 9x+6=-201 | | S(n+6)=-5n | | 7x-2+2x+1=17 | | 18.4x-3.1=16.4+16.9 | | 3(1-2x)=6 | | 3=18d | | 10n(2n+1)-6=20(n-1)+12 | | y=-4/3x-2 | | 2.2x-=2(1.4x+3) | | 6(3r-4)=3/8(46r+8) | | 2b+5=8b-1 | | (2x+3)=14 | | 1/2x+(2x)=3/4 | | -1/-3+4= | | 5f/3=-90 | | P=a+(n+1)b | | -10=2b-7 | | -1/3+4= | | (x-6-(9x-7y))/2x | | 10+[m-6]=7 | | 53/7/31/4 | | 4x+4=7x+37 | | 4x^2+12x+4y^2+16y-119=0 | | 2/3=4/x+2 | | -4x=26 |